Immunology of the Bovine Mammary Gland: Advances in Recent Years - Mavangira, Vengai (The Veterinary clinics of North America. Food animal practice, 2025)
Bovine mastitis remains the most costly disease in the dairy industry due to its impact on milk production, milk quality, and animal welfare. Optimal immunity is essential for the mammary gland to resist infections, efficiently clear them, and limit damage to mammary tissue. This article highlights recent advancements built on previous knowledge exploring opportunities for enhancing mammary gland immune responses. Ultimately, these improvements aim to increase the resistance of the mammary gland to infections and reduce the costs associated with this disease in the dairy industry.